2015
DOI: 10.1128/mbio.01446-15
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Related Protein ATG8 Has a Noncanonical Function for Apicoplast Inheritance in Toxoplasma gondii

Abstract: Autophagy is a catabolic process widely conserved among eukaryotes that permits the rapid degradation of unwanted proteins and organelles through the lysosomal pathway. This mechanism involves the formation of a double-membrane structure called the autophagosome that sequesters cellular components to be degraded. To orchestrate this process, yeasts and animals rely on a conserved set of autophagy-related proteins (ATGs). Key among these factors is ATG8, a cytoplasmic protein that is recruited to nascent autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 58 publications
6
127
1
Order By: Relevance
“…Immunofluorescence images showed that the ATrx1 signal is disrupted; moreover, no apicoplast DNA signal is detectable by DAPI in those parasites (Fig. C), a phenotype consistent with loss of the apicoplast as previously reported by Lévêque et al (Leveque et al , ). A similar pattern is observed with the Golgi in TgDrpC‐HA‐DD parasites grown without Shld1: 85 ± 7% of swollen vacuoles contained parasites in which the Golgi appeared as dispersed puncta in contrast to a solid structure typical of normal parasites (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Immunofluorescence images showed that the ATrx1 signal is disrupted; moreover, no apicoplast DNA signal is detectable by DAPI in those parasites (Fig. C), a phenotype consistent with loss of the apicoplast as previously reported by Lévêque et al (Leveque et al , ). A similar pattern is observed with the Golgi in TgDrpC‐HA‐DD parasites grown without Shld1: 85 ± 7% of swollen vacuoles contained parasites in which the Golgi appeared as dispersed puncta in contrast to a solid structure typical of normal parasites (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Pru strains expressing tdTomato-ATG8 or a tdTomato-ATG8 G124A lipidation mutant were generated by modifying the pTub-tdTomato-TgATG8-CAT plasmid described in Leveque et al 13 via replacement of CAT with BLE and cloning in a larger tubulin promoter fragment encompassing -2730 to -1 relative to the tubulin start codon. Plasmids were linearized with Nar I at -1318 for single crossover integration into the tubulin locus.…”
Section: Methodsmentioning
confidence: 99%
“…Toxoplasma and related apicomplexans including malaria parasites express a limited repertoire of autophagy (ATG) proteins 12 . These parasites also unconventionally require certain ATG proteins for maintenance of the apicoplast 13, 14 , a remnant non-photosynthetic chloroplast. Autophagosome-like structures have been observed under nutrient limiting conditions 15, 16 , but the extent to which the parasite encounters such conditions during infection remains unknown.…”
mentioning
confidence: 99%
“…, ), where it plays a noncanonical role in organelle inheritance during cell division (Lévêque et al . , ). The apicoplast is involved in several key metabolic pathways, so it is essential for the survival of the parasites (Sheiner, Vaidya, & McFadden, ).…”
Section: Introductionmentioning
confidence: 97%